Reducing the number of unnecessary laboratory tests within hospital through the use of educational interventions. (November 2021) - Thurm, Michael; Craggs, Helen; Watts, Merlin; Brooks, Anthony
Background: The growing number of laboratory investigation requests is placing an increased burden upon NHS resources. Around a quarter of all tests are unnecessary repeats, and almost a third have no impact on patient management. Doctors recognise that tests should only be performed when clinically indicated, but a culture persists of undertaking unnecessary repeat investigations. Methods: A cohort study was undertaken at a district general hospital to observe the impact of introducing educational interventions in the form of a poster and a series of educational lectures, encouraging clinicians to consider whether an investigation was clinically indicated. Data was collected from nine different sites across the hospital run by different medical teams regarding the number of tests undertaken and the impact on patient care. Results: Data from over 13, 000 tests and over 2000 patients was analysed from nine different sites across the hospital. There was a significant reduction (33%, p = 0.0001) in the number of blood tests performed. This reduction in testing saved £7006 over the course of 1 month, in addition to other benefits. There was a reduction in testing in eight out of the nine sites in which the study was undertaken, demonstrating good generalisability of results. There was no significant increase in length of admission or mortality. Conclusion: Educational interventions to doctors have a significant and safe impact in reducing the number of unnecessary investigations, providing cost saving benefits to the NHS.